2017
DOI: 10.3390/s17112449
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Optical Biosensors Based on Smartphone Platforms

Abstract: With a rapid improvement of smartphone hardware and software, especially complementary metal oxide semiconductor (CMOS) cameras, many optical biosensors based on smartphone platforms have been presented, which have pushed the development of the point-of-care testing (POCT). Imaging-based and spectrometry-based detection techniques have been widely explored via different approaches. Combined with the smartphone, imaging-based and spectrometry-based methods are currently used to investigate a wide range of molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 48 publications
0
77
1
Order By: Relevance
“…The results are obtained through a smartphone application, which reads the colorimetric results from the strip and provides a positive or negative result based on a cutoff threshold. This biosensing approach has been the subject of several papers, where tools for registration, transfer, and analysis of assays data were discussed [93][94][95][96]. A summary of the patient details and a description of the test taken are given in Figure 9B.…”
Section: Microfluidic-based Ehealthmentioning
confidence: 99%
“…The results are obtained through a smartphone application, which reads the colorimetric results from the strip and provides a positive or negative result based on a cutoff threshold. This biosensing approach has been the subject of several papers, where tools for registration, transfer, and analysis of assays data were discussed [93][94][95][96]. A summary of the patient details and a description of the test taken are given in Figure 9B.…”
Section: Microfluidic-based Ehealthmentioning
confidence: 99%
“…For example, by using the embedded cameras and biosensors, a mobile phone can collect personal information, for example, X-ray and CT images, cough sound, and heart rate, which may be encrypted and compressed before sending to the cloud for training [31], [56]. Review on recent advances in biosensors for mobile health platforms can be found in [122]. The massive number of mobile devices connected to the Internet may relax the limited data sent from an individual phone.…”
Section: A Phone-based Solution For Detection and Surveillancementioning
confidence: 99%
“…[ 248–250 ] The latest models of smartphones incorporate powerful computing capabilities, large data storage, network connectivity, and a large variety of sensors/detectors such as CMOS cameras, touch screens, sound detectors, gyroscopes, etc. Nowadays, the demonstrated smartphone‐based diagnostics include optical microscopy (e.g., brightfield, fluorescence, scattering), [ 251 ] spectroscopy, [ 252 ] colorimetric detection, [ 253 ] and electrochemical detections. [ 254 ] Well‐established tests originally performed with bulky instruments including label‐free immunoassays, cellular imaging, lateral flow assays have been accomplished using such a miniaturized smartphone‐incorporated system.…”
Section: The Roadmap For Future Silicon‐based Optical Biosensorsmentioning
confidence: 99%